Jenis Cedera yang Sering Dialami Jenis Cedera yang Sering Dialami Pemain Bola Voli dan Dampaknya terhadap Performa: Jenis Cedera yang Sering Dialami Pemain Bola Voli dan Dampaknya terhadap Performa - Reza Aofal; Pinton Setya Mustaf; Elsa Ariestika; Shoffurijal Aghyanur (Asosiasi Program Studi Olahraga PGRI Indonesia (APOPI), 2026)
This study aims to identify the types of injuries that are often experienced by volleyball players and analyze their impact on their performance. Injuries in volleyball can reduce the ability of players to perform optimally and risk disrupting their careers. The method used in this study was a survey involving 60 volleyball players from various levels, as well as interviews with coaches and physiotherapists. The results showed that the types of injuries most often experienced by volleyball players were foot injuries (32%), knee injuries (28%), shoulder injuries (20%), hand injuries (15%), and back muscle injuries (5%). The impact of these injuries on player performance is very significant, ranging from reduced agility, attack power, to decreased defensive ability. Players who experience ankle and knee injuries, for example, tend to have difficulty jumping and moving quickly, while shoulder injuries reduce the power and accuracy of smashes. This study suggests the importance of injury prevention through proper warm-up, proper technique, and strengthening relevant muscles to reduce the risk of injury and maintain optimal player performance.